Evaluating the quality of Navigation designed for a WEB site - Sahana, Gorantla; Mary Manasa, ST.; JKR Sastry, Dr; V Chandra Prakash, Dr (International Journal of Engineering and Technology, 2018)
The whole world is looking for information through web sites. Many search engines have come up to help the users locate the content that they are looking for. User satisfaction is most important to ensure frequent visiting and extensive usage of the web site. The user satisfaction is very much dependent on the kind of navigation designed into the web site. The quality of a WEB site is very much dependent on the kind navigation designed into the system. The ease of use could be affected through simple but effective implementation of the navigational system into the WEB site.Quality of a WEB site is the key for establishing effective web sites thereby enhance the businesses. Many factors are to be considered for evaluating the quality of the web sits one such factor is â€œNavigationâ€. Computing the quality of a web site on computational basis is the key to be able to assess the quality of web sites realistically.In this paper, a computational method for computing the quality of the WEB site considering the Navigation built into the WEB site is presented.Â Â